The dual role of the hexosamine biosynthetic pathway in cardiac physiology and pathophysiology - Cairns, Megan; Joseph, Danzil; Essop, M. Faadiel (Frontiers in Endocrinology, 2022)
The heart is a highly metabolic organ with extensive energy demands and hence relies on numerous fuel substrates including fatty acids and glucose. However, oxidative stress is a natural by-product of metabolism that, in excess, can contribute towards DNA damage and poly-ADP-ribose polymerase activation. This activation inhibits key glycolytic enzymes, subsequently shunting glycolytic intermediates into non-oxidative glucose pathways such as the hexosamine biosynthetic pathway (HBP). In this review we provide evidence supporting the dual role of the HBP, i.e. playing a unique role in cardiac physiology and pathophysiology where acute upregulation confers cardioprotection while chronic activation contributes to the onset and progression of cardio-metabolic diseases such as diabetes, hypertrophy, ischemic heart disease, and heart failure. Thus although the HBP has emerged as a novel therapeutic target for such conditions, proposed interventions need to be applied in a context- and pathology-specific manner to avoid any potential drawbacks of relatively low cardiac HBP activity.